2019
DOI: 10.1111/jmg.12468
|View full text |Cite
|
Sign up to set email alerts
|

A paired metamorphic belt in a subduction‐to‐collision orogen: An example from the South Qilian–North Qaidam orogenic belt,NWChina

Abstract: The early Palaeozoic South Qilian–North Qaidam orogenic belt in northwestern China records a nearly complete history of early‐stage long‐lived oceanic subduction–accretion followed by late‐stage continental collision. Most previous studies have focused on low dT/dP metamorphism (HP–UHP) in this belt whereas the paired high dT/dP belt in the hinterland has received little attention. In this contribution, phase equilibrium modelling is combined with zircon petrochronology to determine the P–T–t evolution of gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 114 publications
(307 reference statements)
0
6
0
Order By: Relevance
“…Metamorphic rocks associated with continental‐margin subduction are represented by ca. 470–450 Ma high temperature‐low pressure metamorphic rocks in the Oulongbuluke block and Late Ordovician eclogites along the North Qaidam belt (Li et al., 2019; Song et al., 2019; Zhang et al., 2016). The Tuoxingou accretionary complex contains psammitic schist with Paleoarchean‐Neoproterozoic detrital zircons, also indicating derivation from the adjacent Precambrian microcontent and accumulation along an active continental margin (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metamorphic rocks associated with continental‐margin subduction are represented by ca. 470–450 Ma high temperature‐low pressure metamorphic rocks in the Oulongbuluke block and Late Ordovician eclogites along the North Qaidam belt (Li et al., 2019; Song et al., 2019; Zhang et al., 2016). The Tuoxingou accretionary complex contains psammitic schist with Paleoarchean‐Neoproterozoic detrital zircons, also indicating derivation from the adjacent Precambrian microcontent and accumulation along an active continental margin (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…It occurs at active continental margins and results in the generation of an Andean-type arc-trench system (Ducea et al, 2015;Xiao et al, 2010Xiao et al, , 2020. Subduction of the Proto-Tethys Ocean along a continental margin is recorded by early Paleozoic continental arc magmatic rocks and metamorphic rocks in the Oulongbuluke block and North Qaidam belt (Li et al, 2018b(Li et al, , 2019Wu et al, 2009;Zhu et al, 2010). Continental arc magmatic rocks in the Oulongbuluke block crystallized at ca.…”
Section: Intra-oceanic or Continental Margin Subductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the Palaeozoic orogenic collages in East Asia, such as the Qinling, Qilian and Kunlun orogenic belts indicated that several Precambrian blocks were located on the periphery of the northern margin of eastern Gondwana, which were involved in the evolution of the Proto‐Tethys Ocean during the Early Palaeozoic (e.g., Cawood & Korsch, 2008; Fu et al, 2018, 2019; Li, Niu, et al, 2019; Sun, Dong, et al, 2020; Sun et al, 2022; Xiao et al, 2009; Yan et al, 2015; Yan, Fu, Aitchison, Buckman, et al, 2019, Yan, Fu, Aitchison, Niu, et al, 2019, Yan et al, 2022; Yu et al, 2017, 2019, 2021; Zhang, Zou, et al, 2013; Zhang, Gong, et al, 2013; Zhao et al, 2012; Zhao & Xiao, 2018). The spatial–temporal relationship of these blocks is vital to reasonably understand the evolution of these orogenic belts and the Proto‐Tethys Ocean in the northeastern (NE) Tibet Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…U-Pb ages in zircons can be modified by solid-state dissolution-precipitation and by fluid-driven processes related to metamorphic, hydrothermal or magmatic fluids (Hoskin and Black 2000, Corfu et al 2003, Hoskin 2005, Grant et al 2009, Rubatto 2017). Under regional metamorphism at different P-T conditions, zircon will partially to completely recrystallize or form overgrowth rims, possibly preserving multiple geological episodes in its growth patterns (Bauer et al 2007, Fu et al 2009, Rasmussen et al 2011, Phillips et al 2015, Li et al 2019. Coupled cathodoluminescence imaging and in-situ U-Pb dating allows the identification of metamorphic events within the zircon complex internal textures and growth rims.…”
Section: Introductionmentioning
confidence: 99%